Penal Sanctioning of Zoophilia in Light of the Legal Status of Animals—A Comparative Analysis of Fifteen European Countries - Szilvia Vetter; Anita Boros; László Ózsvári (Animals, 2020)
The criminal legislation regarding zoophilia and the legal status of animals were examined in 15 European countries. With regard to zoophilia, answers to the following questions were sought: are sexual acts performed with animals and the possession and distribution of animal pornography criminally punishable? Several aspects of the legal status of animals were examined including: (1) is the protection of individual animals included in the constitution, (2) do animals have a special status beyond mere objects, (3) can we find specific legislative provisions that explicitly state that animals are not simply things, and (4) does the legal system also take the “dignity” of animals into consideration. The assessment of zoophilia and the legal status of animals resulted in two country rankings, which the authors compared with each other. The correlation was not significant (p = 0.3147). At the same time, countries with differentiated criminal legislation for zoophilia were also 3.62 times more likely to rank higher in terms of the legal status of animals. The Swiss regulations are exceptional in both respects, while at the other end of the list, Italy does not have specific legislative provisions for either aspect.